## d/dx (csc x)

### To find the derivative of the function f(x) = csc(x), where csc(x) represents the cosecant of x, we can apply the quotient rule

To find the derivative of the function f(x) = csc(x), where csc(x) represents the cosecant of x, we can apply the quotient rule. Recall that the quotient rule states:

If f(x) = g(x) / h(x), then f'(x) = (g'(x) * h(x) – g(x) * h'(x)) / (h(x))^2.

In the case of f(x) = csc(x), we can rewrite it as f(x) = 1 / sin(x), since csc(x) is the reciprocal of sin(x). Now, let’s apply the quotient rule:

g(x) = 1

h(x) = sin(x)

Finding the derivatives:

g'(x) = 0 (since the derivative of a constant is zero)

h'(x) = cos(x) (since the derivative of sin(x) is cos(x))

Now we can substitute these values into the quotient rule formula:

f'(x) = (0 * sin(x) – 1 * cos(x)) / (sin(x))^2

= -cos(x) / sin^2(x)

= -cos(x) / sin(x) * sin(x)

= -cos(x) / sin(x) * 1 / sin(x)

= -cot(x) / sin(x)

Therefore, the derivative of csc(x) with respect to x is -cot(x) / sin(x).

##### More Answers:

Differentiate tan(x) using the quotient rule and find the derivative of tan(x) with respect to xHow to Find the Derivative of the Cotangent Function using the Quotient Rule

Understanding the Derivative of the Secant Function | Step-by-Step Quotient Rule Application